A zero carbon route to the supply of high-temperature heat through the integration of solid oxide electrolysis cells and H2–O2 combustion. (October 2022) - Zhang, Shuhao; Zhang, Nan; Smith, Robin; Wang, Wanrong
Abstract: Previously suggested options to achieve carbon neutrality involve the use of fossil fuels with carbon capture or exploiting biomass as sources of energy. Industrial high-temperature heating could possibly exploit electrical heating or combustion using hydrogen. However, it is difficult to replace all the current coal or natural gas furnaces with these options for chemical industry. In this work, a method that integrates solid oxide electrolysis cells (SOEC) and H2 –O2 combustion is proposed, and the related parameters are modelled to analyze their impacts. There is no waste heat and waste emissions in the proposed option, and all substances are recycled. Unlike previous research, the heat required for SOEC operation is generated from H2 combustion. The best working condition is under thermoneutral voltage, and the highest electricity-to-thermal efficiency that can be achieved is 86.88% under a current density of 12000 A/m 2 and operating temperature of 750 °C. Ohmic overpotential has the greatest effect on electricity consumption, and the anode activation overpotential is the second most important option. Increasing combustion product temperature cannot significantly improve thermal efficiency, but can raise the available maximum thermal energy. Graphical abstract: Image 1 Highlights: First time to integrate solid oxide electrolysis cells and hydrogen-oxygen combustor together to convert electricity to high-temperature thermal energy for the chemical industry without carbon emission. Analyze the influence of current density and SOEC temperature on hydrogen production rate and energy efficiency. Discuss the influence of combustion product temperature on efficiency, waste heat and pollutants.